2015
DOI: 10.1617/s11527-015-0749-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on local bond stress-slip relationship in self-compacting concrete

Abstract: This paper summarizes the results of an experimental study on local bond stressslip relationship of deformed reinforcing bars embedded in self-compacting concrete, considering the effect of concrete confinement by transverse reinforcement. In this study were cast 104 specimens by using self-compacting concrete and vibrated concrete. Pull-out tests were performed on deformed bars with short anchorage length (ld ≤ 5∅). The parameters analyzed were the concrete type, the confining reinforcement, the bar diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Previous studies have reported an increase in bond strength with increase in confining pressure [20,28,27,37,39], yet it tends to level off at ratios of σl,cc/fc of between about 0.25 and 0.30, where σl,cc is the lateral confining stress and fc is the concrete strength.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have reported an increase in bond strength with increase in confining pressure [20,28,27,37,39], yet it tends to level off at ratios of σl,cc/fc of between about 0.25 and 0.30, where σl,cc is the lateral confining stress and fc is the concrete strength.…”
Section: Introductionmentioning
confidence: 95%
“…In such tests, premature splitting failures can be arrested through confining action by stirrups [27,28] or external devices [29][30][31]. Tests showed nonetheless that the bond strength exhibits an upper bound, since there is a limit of confining pressure which forces bond failure due to shearing of the concrete keys between the rebar ribs [26,29].…”
Section: Introductionmentioning
confidence: 99%
“…The bond strength between reinforcing bars and SCC is mainly derived from friction, chemical adhesion and mechanical interlock resistance of the interface [49]. The failure of mechanical interlock bond resulting from the steel rebar and concrete leads to the concrete being split (low strength of concrete or insufficient thickness of protective layer) or the steel bar being pulled out (the concrete around the interface being shear damage due to the high elastic modulus and the shear strength of steel bar) [50,51]. Muñoz [52] showed that the bond behavior and damage mechanism of FRP bars and concrete were different from that of traditional steel bars owing to the low elastic modulus and shear strength of FRP bars.…”
Section: Principle Of Damage Detection Of Bond-slip Behaviormentioning
confidence: 99%
“…For relatively large couplers, the local reinforcement ratio at the coupler section ρs,co in conjunction with its bond characteristics τb,co, in comparison with the actual reinforcement ratio ρs,b at the rebar section combined with its surface type τb, have a direct effect on the crack spacing and kinematics. A comparative study on the influence of the size factor λs=dcLc/(dbLb) on the crack spacing ratio λco is presented below by considering a range of coupler configurations, with the relevant details extracted from available data sheets [28,29,[51][52][53][54][55][56][57][58][59][60]. The coupler and rebar geometries were used to assess ρs,b, ρs,co and the crack spacing ratio λco=sr0,b/sr0,co in which sr0,b is the crack spacing at the rebar region, while sr0,co represents the crack spacing at the coupler region.…”
Section: Cracking Characteristicsmentioning
confidence: 99%